Ecology of saprotrophic basidiomycetes - Boddy, Lynne; Frankland, Juliet C.; West, P. van (Pieter) (British Mycological Society symposium series, 2008)
The breadth and depth of understanding of many areas concerning basidiomycetes has increased dramatically since the premier publication of Frankland et al., Decomposer Basidiomycetes: their Biology and Ecology. New vistas have opened up with the advent of powerful computing, modelling and molecular approaches helping to greatly increase the general understanding of the ecology of basidiomycetes. This is tantamount to understanding the role of fungi in natural ecosystems since they are major agents of decomposition and nutrient cycling. These remarcable advances have been incorporated into this volume that discusses all aspects of saprotrophic basidiomycete ecology.